WISDOM LOCAL EMPOWERMENT IN SUSTAINABLE DEVELOPMENT PERSPECTIVE - Mawardi, Ichwanudin (BPPT)
Local wisdom is the people knowledge which comes from long evolved period between the people and their environment. Local wisdom by the some people is made as a basis in environment management based on sustainable development. Technology advancement in globalization era has impact to the development and existence of local wisdom, are values or the customs are considered have been outdated compared to the modern age advancement. On the other side, in fact the if reviewed the principles and concept of local wisdoms can live side bi side with this globalization era, even they can be made as a reference for the sustainable development, certainly after they going through empowerment of values and the local wisdom. Empowerment of local wisdomcan be conducted through various aspect such as : enhancing local values through application and utilization of advanced technology, strengthening people institutional of those who manage natural resources, enforcing implementation through establish of regulations (positive law) and so on.keywords : local wisdom, sustainable development, management based on people